2008
DOI: 10.1021/es702247q
|View full text |Cite
|
Sign up to set email alerts
|

Emission Characteristics of Carbonaceous Particles from Various Residential Coal-Stoves in China

Abstract: China is thought to be the most important contributor to the global burden of carbonaceous aerosols, and residential coal combustion is the greatest emission source of black carbon (BC). In the present study, two high-efficiency household coalstovesaretestedtogetherwithhoneycomb-coal-briquettesandrawcoal-chunks of nine different coals. Coal-burning emissions are collected onto quartz fiber filters (QFFs) and analyzed by a thermal-optical transmittance (TOT) method. Emission factors (EFs) of particulate matter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
147
5
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 174 publications
(166 citation statements)
references
References 23 publications
(66 reference statements)
12
147
5
2
Order By: Relevance
“…Both designs increased chances of volatile matter in fuels for complete combustion, and hence the emission reduction (especially BC) (11).…”
Section: Resultsmentioning
confidence: 99%
“…Both designs increased chances of volatile matter in fuels for complete combustion, and hence the emission reduction (especially BC) (11).…”
Section: Resultsmentioning
confidence: 99%
“…Since a previous study had demonstrated that EC concentrations were comparable to BC measured by an optical method (Aethalometer AE90) for 11 coal/stove combinations (25), BC was considered as the same mass as EC in this study.…”
Section: Methodsmentioning
confidence: 99%
“…That is, BC would exert a more intensive dome effect over rural surface. It should be noted that residential combustion of raw coal and biofuel in a small domestic stove in rural area is responsible for the majority of BC emission in China (Zhi et al, 2008;Li et al, 2017a). More 10 stable PBL and more significant dome effect over rural surface would further favor the formation and accumulation of regional air pollution.…”
Section: A Comparison Of the Dome Effect Over Urban And Rural Areasmentioning
confidence: 99%